A soldier in Arabia a British military memoir from Jordan to Saudi Arabia - Bromage, Nigel (Radcliffe Press, 2012)
A Soldier in Arabia is a revealing personal memoir of the Middle East, but much more - it sheds light, through dramatic and authentic personal experience, on how Britain pursued its interests in the enduring struggles of the Middle East first via highly trained and committed military officers.